TAREKAT ALAWIYYAH DI KALIMANTAN SELATAN: SEBUAH TELAAH UNSUR NEO-SUFISME DALAM TAREKAT - Hakim, Abdul (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
As a known tarekat, the tarekat 'Alawiyah basically insists on planting experience of shariah and noble character. Tarekat Alawiyah in South Kalimantan taught by teacher Bachiet also emphasized the moral aspect of his disciples. Moral formation was through the Majelis taklim assemblies. Among its activities are sympathize widows, orphans and habaib. The establishment of moral and social activity is an essential element in the neo-Sufism. In addition, remembrance and carried muraqabah also an element of neo-Sufism. But the use of the dzikir of isim mufrad and dhamir